Exploring the possible use of saponin adjuvants in COVID-19 vaccine. Issue 12 (1st December 2020) - Sharma, Rinku; Palanisamy, Arivukarasu; Dhama, Kuldeep; Mal, Gorakh; Singh, Birbal; Singh, Karam Pal
ABSTRACT: There is an urgent need for a safe, efficacious, and cost-effective vaccine for the coronavirus disease 2019 (COVID-19) pandemic caused by novel coronavirus strain, severe acute respiratory syndrome-2 (SARS-CoV-2). The protective immunity of certain types of vaccines can be enhanced by the addition of adjuvants. Many diverse classes of compounds have been identified as adjuvants, including mineral salts, microbial products, emulsions, saponins, cytokines, polymers, microparticles, and liposomes. Several saponins have been shown to stimulate both the Th1-type immune response and the production of cytotoxic T lymphocytes against endogenous antigens, making them very useful for subunit vaccines, especially those for intracellular pathogens. In this review, we discuss the structural characteristics, mechanisms of action, structure–activity relationship of saponins, biological activities, and use of saponins in various viral vaccines and their applicability to a SARS-CoV-2 vaccine.